Comparison of wet versus dry feeding for starter pigs - Thaler, R.C.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies utilizing a total of 480 pigs (21 days old) were conducted to compare wet versus dry feeding during a 4 wk starter period. Pigs were fed a pelletized, high nutrient density diet for the first 2 wk and a semi-complex diet (meal form) for the last 2 wk. Aqua® feeders were used in all pens. During the first 2 wk of the study, feeding method had no effect on daily gain or feed intake; however, pigs fed dry diets required less feed per pound of gain than did pigs consuming wet diets (P<.0002). For the overall 4 wk trial, gains and feed intake did not differ between treatments, but pigs fed the wet diets were less efficient than pigs receiving the dry diets. Based on these results, wet feeding is not advantageous to starter pig performance.
Keywords: Swine; Starter pig; Wet feeding; Performance